2010
DOI: 10.1021/jo100640w
|View full text |Cite
|
Sign up to set email alerts
|

Tetrathiomolybdate Mediated Rearrangement of Aziridinemethanol Tosylates: A Thia-Aza-Payne Rearrangement

Abstract: Aziridinemethanol sulfonate esters react with tetrathiomolybdate 1 to give thiirane derivatives as the major product and cyclic disulfides as minor product under mild reaction conditions via an unprecedented thia-aza-Payne-type rearrangement. Interestingly, when the reaction of 1 was carried out with 2-aziridino-cyclohexanol derivatives it resulted in the formation of thia-bicyclo[3.1.1]heptane or dithia-bicyclo[3.2.1]octane derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…After the ring-opening with ammonium tetrathiomolybdate and subsequent intramolecular cyclization, the compound was converted into a bridged thietane 183 in 75% yield. The results indicated that, in the ring-opening step, tetrathiomolybdate nucleophilically attacked the more substituted aziridine carbon atom [62] (Scheme 37). The thioetherification cyclization of 1,3-dihaloalkanes, 3-haloalkyl sulfonates, or disulfonates of alkane-1,3-diols with sodium sulfide is a common method for the preparation of thietanes.…”
Section: Synthesis Via the Nucleophilic Ring-opening Of Threememberedmentioning
confidence: 99%
“…After the ring-opening with ammonium tetrathiomolybdate and subsequent intramolecular cyclization, the compound was converted into a bridged thietane 183 in 75% yield. The results indicated that, in the ring-opening step, tetrathiomolybdate nucleophilically attacked the more substituted aziridine carbon atom [62] (Scheme 37). The thioetherification cyclization of 1,3-dihaloalkanes, 3-haloalkyl sulfonates, or disulfonates of alkane-1,3-diols with sodium sulfide is a common method for the preparation of thietanes.…”
Section: Synthesis Via the Nucleophilic Ring-opening Of Threememberedmentioning
confidence: 99%
“…The “aza‐Payne rearrangement”, however, implying the conversion of a 2‐(hydroxymethyl)aziridine into its isomeric oxirane or vice versa, and the “thia‐Payne rearrangement”, referring to the equilibrium between a 2‐(hydroxymethyl)thiirane and an epoxide, can be tuned and controlled to a certain extent depending on the applied reaction conditions. Despite numerous papers reporting epoxide–aziridine and/or epoxide–thiirane migrations, only one article dealing with an aziridine‐to‐thiirane rearrangement has been published so far . Moreover, the transformations in that particular study appeared to induce the formation of side products as well, as treatment of a variety of polysubstituted 1‐tosyl‐2‐(tosyloxymethyl)aziridines with an excess amount of benzyltriethylammonium tetrathiomolybdate ([BnEt 3 N] 2 MoS 4 ) in CH 3 CN afforded the corresponding thiiranes as the major products (75–80 %) and cyclic disulfides as the minor compounds (20–25 %).…”
Section: Introductionmentioning
confidence: 99%